Disparities in female breast cancer mortality rates in Brazil between 1980 and 2009 - Freitas-Junior, Ruffo (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2012)
OBJECTIVE: To describe the temporal trends in female breast cancer mortality rates in Brazil in its macro-regions and states between 1980 and 2009. METHODS: This was an ecological time-series study using data on breast cancer deaths registered in the Mortality Data System (SIM/WHO) and census data on the resident population collected by the Brazilian Institute of Geography and Statistics (IBGE/WHO). Joinpoint regression analyses were used to identify the significant changes in trends and to estimate the annual percentage change (APC) in mortality rates. RESULTS: Female breast cancer mortality rates in Brazil tended to stabilize from 1994 onward (APC = 0.4%). Considering the Brazilian macro-regions, the annual mortality rates decreased in the Southeast, stabilized in the South and increased in the Northeast, North, and Midwest. Only the states of Sao Paulo (APC = -1.9%), Rio Grande do Sul (APC = -0.8%) and Rio de Janeiro (APC = -0.6%) presented a significant decline in mortality rates. The greatest increases were found in Maranhao (APC = 12%), Paraiba (APC = 11.9%), and Piaui (APC = 10.9%). CONCLUSION: Although there has been a trend toward stabilization in female breast cancer mortality rates in Brazil, when the mortality rate of each macro-region and state is analyzed individually, considerable inequalities are found, with rate decline or stabilization in states with higher socioeconomic levels and a substantial increase in those with lower socioeconomic levels.